Structures Congress 2013 2013
DOI: 10.1061/9780784412848.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Truck Types using Strain Sensors include Co-located Strain Gauges

Abstract: A bridge's performance depends on different factors including superstructure type, support conditions, construction materials, environmental conditions and external loading. Identifying and evaluating the loads applied to a bridge, during its effective life, are necessary for assessing the condition and remaining life of that bridge. Furthermore, the influence of dynamic loading on the structural response of the bridge is important to be considered for the safety of the structure. Although ambient loads can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Examples indicated that all vehicles across the bridge were identified with an acceptable accuracy and the statistical distribution of vehicle weight was in good agreement with the actual one. Zolghadri et al (2013) applied the B-WIM system with multiple sensors installed on a single-span prestressed concrete bridge for vehicle weight identification.…”
Section: Introductionmentioning
confidence: 99%
“…Examples indicated that all vehicles across the bridge were identified with an acceptable accuracy and the statistical distribution of vehicle weight was in good agreement with the actual one. Zolghadri et al (2013) applied the B-WIM system with multiple sensors installed on a single-span prestressed concrete bridge for vehicle weight identification.…”
Section: Introductionmentioning
confidence: 99%
“…As for the speed estimation, peak-to-peak approach proposed in WAVE project (O'Brien and Žnidarič 2001) has been widely implemented (Cardini and DeWolf 2009, Brown 2011, Zolghadri et al 2013, Richardson et al 2014. The speed is calculated from the time difference of peaks from the strain signals collected at two longitudinal locations.…”
Section: Introductionmentioning
confidence: 99%